Economic evaluation of the replacement of sugar cane bagasse by vinasse, as a source of energy in a power plant in the state of Paraná, Brazil. (September 2017) - Pazuch, Felix Augusto; Nogueira, Carlos Eduardo Camargo; Souza, Samuel Nelson Melegari; Micuanski, Viviane Cavaler; Friedrich, Leandro; Lenz, Anderson Miguel
Abstract: Sugarcane had its participation in the Brazilian energy sector boosted when PROÁLCOOL was enacted, a program that encourages the production of ethanol fuel made from sugarcane. The ethanol production process generates a residue in large proportions, called vinasse. This study aimed to assess the economic feasibility of using vinasse to produce electricity in an ethanol plant located in the northwestern region of the state of Paraná, Brazil. The electricity generated will be consumed by the plant itself, and the sugarcane bagasse, which was used to be burned in a boiler to generate that electricity, will now be sold to other consumers. The study was conducted considering two operating modes. For each operation, it was considered five scenarios, ranging from the most optimistic (highest salesprice per ton of sugarcane bagasse) to the most pessimistic (lowest sales price per ton of sugarcane bagasse). It was calculated the feasibility of the project by using the Internal Rate of Return (IRR), Net Present Value (NPV) and the discounted payback period. All indexes indicated great economic feasibility to project development. It was conducted an NPV sensitivity analysis considering the variation of the sales price of sugarcane bagasse, the quantity sold and the fixed costs involved. It was also carried out a Probability Analysis, using 1000 NPV simulations, considering that the change in the selling price of the bagasse has a normal distribution. The energy production cost for the expected scenario in Operations 1 and 2 were, respectively, US$51.98MWh −1 and US$ 86.64MWh −1 .